Protective Role of Tridax Procumbens against Adjuvant Induced Arthritis in a Murine Model: Pharmaceutical Sciences-Microbiology for health care - Rao, K. Gopal; Rao, Y.R.K Tirupathi; chandra, A .Satish (International Journal of Life Science and Pharma Research, 2021)
Rheumatoid arthritis is the inflammatory disease affecting the joints and imposes significant burden among the individuals. Oxidative stress is one of the major mechanisms involved in the progression of arthritis. It is postulated that inflammation and secretion of various inflammatory cytokines also plays pivotal role in rheumatoid arthritis. Tridax procumbens (Asteraceae) is one of the potent herb and possess various biological actions. So, the present study was carried out to evaluate the protective role of Tridax procumbens in a murine model of complete Freund’s adjuvant (CFA) provoked arthritis. The rats were made arthritic by injecting 0.1ml CFA into rat hind paw by intradermal route. Tridax procumbens methanolic extract (200 and 400 mg/kg, b.wt) were administered orally daily for 28 days after induction of arthritis. The anti arthritic effect was evaluated by, alterations in paw volume and body weight, changes in hematological parameters, increased lipid peroxidation and decreased antioxidants (SOD, CAT, GPx and GSH) due to arthritis. Treatment with Tridax procumbens significantly reduced the paw volume and increased the body weight in arthritic rats. Further, treatment with Tridax procumbens significantly increased the RBC and hemoglobin and decreased the WBC and ESR level as compared to the arthritic rats. The antioxidant levels were significantly increased in arthritic rats after treatment with extracts. Thus the anti-arthritic potential of Tridax procumbens might be mediated through antioxidant and anti-inflammatory effect of the extracts